KONSEP SANG PENYELAMAT DALAM TEOLOGI ISLAM DAN YAHUDI (STUDI INTERTEKSTUALITAS JULIA KRISTEVA) - Bayu Paizin, Harel (Mazalat: Jurnal Pemikiran Islam, 2024)
This article discusses on discourse of intended Savior in Islamic sacred text (Hadith) and Jewish Sacred text (Old Testament). The texts are analysed from semiotic perspective which is introduced by Julia Kristeva. The texts are such a world history, and we can say that both of them related each other because all of texts are influenced by other texts. The article specially attempts to discribe composition of both of texts. The article shows that there are similarities and differences on concept of The Savior in both of tradition. The Savior in Islamic tradition is for all human, while  The Savior in Jewish Tradition is only for Jewish. In other hand, they have similarity on concept of the savior in related to time of when he will come to the human and his function to fix distruption in the world.